Investigating Information Integrity: Pathways for researching informational practices on digital platforms - Ballardin, Bernardo Martinho; Senne, Fabio Jose Novaes de (AoIR Selected Papers of Internet Research, 2026)
As much as the debate around contemporary information flows and its associated risks has advanced in the last years—specially through the consolidation of an “information integrity” agenda—there are still significative gaps in literature concerning how digital platform usage affects the access to reliable, diverse and evidence-based information. Building on this, the present article aims to contribute to the discussion on how digital platforms’ big data algorithmic infrastructures relate to the promotion of healthy and diverse informational ecosystems. It draws upon existing sociological literature about algorithmic systems and on accumulated knowledge from international discussions (regarding the elaboration of an information integrity-oriented survey) to build an “investigation matrix”, proposing pathways for future practical quantitative and qualitative research in the field. Among its many conclusions, the matrix reinforces the need for a more holistic articulation of efforts on the theme, as well as the importance of multidisciplinary research that encompasses both the technical and social aspects of the phenomena. The article also discusses the importance of digital platforms in aiding researchers and policymakers with access to data, enabling impactful research efforts in the field.